Impact of Clinical Presentation on Imaging Evaluation to Direct Effective Treatment Strategies - Roller, Brandon L.; Schumacher, Christopher W. V.; Torabi, Maha; Lenchik, Leon; Ferguson, Cristin M. (The Journal of Knee Surgery, 2018)
A multitude of musculoskeletal disorders of the knee are commonly encountered in clinical practice. Ensuring an accurate diagnosis can be challenging. It is critical to establish a thoughtful and systematic approach to assessing the patient using history and physical exam followed by appropriate imaging studies. The physical exam may be complicated due to various test maneuvers designed to help make the diagnosis. It is also important to understand the limitations of each physical exam maneuver. When appropriate, imaging is obtained to help make the diagnosis and guide treatment. There are various imaging examinations to choose from when evaluating the knee, including X-rays, computed tomography, magnetic resonance imaging, and ultrasound. An algorithmic approach to choosing the best imaging study is often helpful to avoid unnecessary costs and burden to the patients. The combination of a thorough clinical assessment and appropriate imaging examinations will result in accurate diagnosis, which directs proper treatment.
Keywords: knee examination; imaging; MRI; ultrasound